Financial Performance and Socio-Economic Contributions of Income-Generating Projects of State Universities and Colleges - Mendoza, Donna (Technium Business and Management, 2023)
Income-generating projects have been introduced, played a crucial role in education, and improved public universities' financial performance. The full realization of their potential was impossible due to several bottlenecks. This research employed the descriptive design using a survey questionnaire and secondary data using total population sampling to assess the financial performance of income-generating projects of SUCs based on their profitability, liquidity, and solvency. The results revealed that the financial performance of Income-Generating Projects (IGPs) among State Universities and Colleges (SUCs) is satisfactory. Based on the results, although the profitability ratios yielded positive revenue figures, it needs to be more consistent, particularly in maintaining its profit. Nevertheless, the positive results indicate that these SUCs have an excellent financial position regarding liquidity and solvency. These IGPs play a pivotal role in diversifying revenue streams for SUCs in accumulating additional income. By generating income through innovative initiatives, these institutions can reduce their reliance on traditional funding sources, creating a more sustainable financial foundation. Thus, the socio-economic contributions of IGPs depend on the financial performance of the IGPs. Ultimately, the findings strongly suggested improving the IGP's financial performance. Therefore, crafting an action plan for IGPs to enhance their financial performance further is sought.